Analisis Pengaruh Bauran Pemasaran Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Konsumen (Studi Kasus Pada Skyways Coffee & Creative Space Payakumbuh) - Hasbi, Imanuddin; Anilawati, Hizrina (eProceedings of Management, 2025)
AbstractThe coffee shop business sector in Indonesia continues to grow rapidly, including in smaller cities such asPayakumbuh. Skyways Coffee & Creative Space offers a unique concept that not only serves a variety of coffee butalso provides a creative space for visitors to collaborate. However, Skyways faces the challenge of declining salesover the past year. Customer reviews and pre-survey results indicate a significant gap between customer perceptionsof the marketing mix and the quality of service provided. This study aims to analyze the influence of the marketing mixand service quality on purchasing decisions at Skyways. Using a quantitative approach, the research involved 300respondents selected through non-probability sampling methods. The data were analyzed using statistical techniques,including multiple linear regression, with the aid of SPSS software. The study results show that both the marketingmix and service quality have a significant influence, both partially and simultaneously, on purchasing decisions.Nevertheless, to enhance competitiveness and attract more customers, attention is needed on other factors such asconsumer income levels, the presence of competitors, customer loyalty programs, and the use of digital technology inproduct innovation, promotions, and services.Keywords-marketing mix, service quality, consumer purchasing decisions